A radiobiological study of carbon ions of different linear energy transfer in resistant human malignant cell lines. (1st November 2020) - Petrović, Ivan M.; Ristić Fira, Aleksandra M.; Keta, Otilija D.; Petković, Vladana D.; Petringa, Giada; Cirrone, Pablo; Cuttone, Giacomo
Abstract: Purpose: Analysis of elimination of four human radioresistant malignant cell lines to mono-energetic and non mono-energetic incoming carbon ion beams, characterized by different linear energy transfer (LET) qualities is performed. Comparisons with protons from the middle of the therapeutic spread out Bragg peak (SOBP) and reference γ-rays are also included. Materials and methods: HTB140 cells were irradiated at five positions, with different LET, along the 62 MeV carbon pristine Bragg peak. To provide reliable reproducibility of irradiations at INFN-LNS, as the carbon Bragg peak is very narrow, precise positioning of samples for desired LET value is complicated. The peak was slightly widened using two ripple filters. After defining irradiation position and LET at the peak itself where cell killing is almost the highest, irradiation position with the same LET value was found within somewhat broadened peak. HTB140, MCF-7, HTB177 and CRL5876 cells were irradiated at the two described positions. Additionally, irradiations in the middle of 62 MeV proton SOBP and reference γ-rays were performed. Doses ranged from 0.5 to 16 Gy. Cell survival and corresponding radiobiological parameters were assessed seven days after irradiations. Results: When moving irradiation position along the carbon Bragg curve, LET rises from 85 to 747 keV/µm, while surviving fraction at 2 Gy (SF2) for HTB140 cells, falls from 0.72 to 0.57 further rising to 0.73 on the distal fall-off part of the curve. Improved cell radiosensitivity is seen for the doses below 4 Gy. Relative biological effectiveness (RBE) increases from 4.56 to 7.69 and drops to 4.23. Almost the highest cell killing LET, being ∼200 keV/µm, is used to irradiate HTB140, MCF-7, HTB177 and CRL5876 cells within the pristine and slightly broadened Bragg peak. After irradiations with protons of the mid SOBP, carbon ions of the pristine and slightly widened Bragg peak RBE ranges for HTB140 cells from 2.08, 4.81 to 7.06, for MCF-7 from 1.70, 3.28 to 4.17, for HTB177 from 1.98, 4.18 to 5.08 and for CRL5876 from 1.33, 2.57 to 3.51. Conclusions: Significant elimination of HTB140 cells is observed along the carbon Bragg curve. The highest one is achieved by LET that is at the level of already reported. For the same LET, mono-energetic carbon ions provide higher cell elimination than the non mono-energetic. For all cell lines, both carbon ion beams, more the monoenergetic one, express stronger killing rate than protons and especially γ-rays.